Analysis of the Health of Islamic Banking in Indonesia - Sandi Nasrudin Wibowo; Yodi Rudiantono (IJESS International Journal of Education and Social Science, 2022)
This study aims to determine the soundness of Islamic Commercial Banks using the measurement method regulated in Bank Indonesia Regulation PBI No.13/1/PBI/2011, concerning Assessment of Bank Soundness Levels using the RGEC method. The assessment factors in the RGEC method are the risk profile factor (bank risk), the Good Corporate Governance (GCG) factor, the earnings factor (profitability) and the capital factor (capital). The object of this research isFinancial Statements of Bank Muamalat Indonesia and Bank BJB Syariah from 2015 to 2018. The analysis technique in this study is quantitative descriptive by calculating financial ratios using the RGEC method. The results of this study indicate that Bank Muamalat and Bank BJB Syariah, show the period from 2015 to 2018 in the fairly healthy category.